A study on the artificial insemination interview experience of nursing students in the COVID-19 situation - So Young Park; Miyoung Park; Nam Young Choi; Sun Jung Park (Tehran University of Medical Sciences, 2022)
Background & Aim: The purpose of this study is to examine the perception of artificial insemination interviews experienced by prospective nursing graduates who have experienced artificial insemination interviews at medical institutions using focus groups and provide necessary data to increase the efficiency of artificial insemination interviews. Methods & Materials: This study was conducted to examine the artificial insemination interview experience of nursing students in the midst of COVID-19 by performing a focus group interview and qualitative content analysis. The focus group interview was carried out on November 17, 2021, to understand the artificial insemination interview experience of nursing students during COVID-19, selecting a total of 14 senior nursing students. Results: As a result of analyzing the artificial insemination interview experiences of nursing students who participated in this study, 35 codes, grouped into 8 subcategories, were derived. They are also classified into 3 categories 1) Finding your way in the dark, 2) Confronting artificial intelligence, and 3) Going beyond artificial intelligence. The eight subcategories derived are as follows: 1) Vagueness, 2) Find your way, 3) The fight between artificial intelligence and me, 4) Strong questions about interview evaluation, 5) New experience, 6) Learn your own tricks for artificial insemination interviews, 7) Setting up the environment for artificial insemination interview, 8) Establishment of information system for artificial insemination interview. Conclusion: Based on the results of this study, an educational program should be developed based on the main data obtained from the artificial insemination interview experience so that nursing college students can adapt to the artificial insemination interview.